2015
DOI: 10.1111/soc4.12294
|View full text |Cite
|
Sign up to set email alerts
|

Twitter and Political Campaigning

Abstract: The use of Twitter by politicians, parties, and the general audience in politics, particularly during election campaigns, has become an extremely popular research field almost overnight. Even though Twitter, a medium that emerged early in 2006 -the first tweet was posted on 21 March 2006 by Jack Dorsey, co-founder of Twitter -and elections occurring only every few years, it has already received much academic attention. The studies produced are very diverse, ranging from analyzing how politicians or citizens us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 72 publications
6
44
0
17
Order By: Relevance
“…En la campaña de las elecciones generales de 2016, los candidatos emplean profusamente las funciones de interacción de que dispone Twitter, especialmente el retweet y la mención, lo que parece no concordar con los trabajos que hablan de una limitada interacción por parte de los políticos (Graham et al, 2013;Stromer-Galley, 2014;Vergeer, 2015). Sin embargo este uso, pese a su abundancia, no busca realmente propiciar un diálogo con los ciudadanos u otros actores al margen de los partidos, sino que se emplea con una finalidad autorreferencial o de interacción intrapartido.…”
Section: Discusión Y Conclusionesunclassified
“…En la campaña de las elecciones generales de 2016, los candidatos emplean profusamente las funciones de interacción de que dispone Twitter, especialmente el retweet y la mención, lo que parece no concordar con los trabajos que hablan de una limitada interacción por parte de los políticos (Graham et al, 2013;Stromer-Galley, 2014;Vergeer, 2015). Sin embargo este uso, pese a su abundancia, no busca realmente propiciar un diálogo con los ciudadanos u otros actores al margen de los partidos, sino que se emplea con una finalidad autorreferencial o de interacción intrapartido.…”
Section: Discusión Y Conclusionesunclassified
“…En el ámbito internacional, contamos con ya con abundantes trabajos significativos ligados con procesos electorales en diversos países, por ejemplo respecto de EEUU (Hendriks & Kay, 2010;Vargo, Guo, McCombs & Shaw, 2014); Italia (Ceron & d'Adda, 2015;Vaccari & Valeriani, 2015); Francia (Mercier, 2015); Bélgica (D'Heer & Verdegem, 2014) u Holanda (Vergeer & Hermans, 2013); entre muchos otros. De hecho, se trata de un campo tan fructífero que podemos encontrarnos incluso con trabajos cuyo propósito es compilar las aportaciones más relevantes (Vergeer, 2015).…”
Section: El Nuevo Ecosistema Comunicativo Y El Papel De Twitter En Caunclassified
“…Existing research suggests that politicians rarely do either of these two, since they neither use social networks to inform citizens of their policies, nor communicate personal information which would allow voters to get a better understanding of who they 'really' are (Larsson, 2015;Momoc, 2013;Ross et al, 2015). Rather, studies found that politicians often use social media as a public relations tool for relaying information about the campaign, and in that sense, mirror the 'offline', traditional promotional strategies (see also Vergeer, 2015;Zamora Medina & Zurutuza Munoz, 2014).…”
Section: Techniques Of Impression Managementmentioning
confidence: 99%